Long-Term Protection Against Tobacco Mosaic Virus Induced by the Marine Alga Oligo-Sulphated-Galactan Poly-Ga in Tobacco Plants - Matsuhiro-Yamamoto, B; Matsuhiro-Yamamoto, B; Zuniga-Navarro, G; Moenne-Munoz, A; Barrientos-Carvacho, H; Barrientos-Carvacho, H; Gonzalez-Figueroa, A (2011)
In order to study the antiviral effect of the oligo-sulphated galactan Poly-Ga, the leaves of tobacco plants XhantiNN were sprayed with water (control), with increasing concentrations of Poly-Ga, for increasing numbers of treatments or cultivated for increasing times after treatment. Control and treated plants were infected with tobacco mosaic virus (TMV) and the numbers of necrotic lesions were measured in infected leaves. The number of necrotic lesions decreased with increasing concentrations of Poly-Ga, with increasing numbers of treatments and with increasing time after treatment, indicating a long-term protection against TMV that mimicks vaccination. In addition, control Xhantinn plants and plants treated with Poly-Ga and cultivated for increasing times after treatment were infected with TMV in the middle part of the plant, and the levels of TMV-capsid protein (CP) transcripts were measured in apical leaves. TMV-CP transcripts decreased in distant leaves, indicating that Poly-Ga induces systemic protection against TMV. The activities of the defence enzymes phenylalanine ammonia lyase (PAL) and lipoxygenase (LOX) and the amounts of several phenylpropanoid compounds (PPCs) were measured in control and treated plants without infection. A progressive increase in PAL activity was observed with increasing time after treatment, together with the accumulation of free and conjugated PPCs. In contrast, LOX activity remained unchanged. Interestingly, the increase in PAL activity showed a linear correlation with the decrease in necrotic lesions and the decrease in TMV-CP transcript level. Thus, Poly-Ga induced systemic and long-term protection against TMV in tobacco plants that is determined, at least in part, by a sustained activation of PAL and the accumulation of PPCs with potential antiviral activity. © 2011 The Authors. Molecular Plant Pathology © 2011 BSPP and Blackwell Publishing Ltd.